DUE PROCESS OF LAW IN EUROPEAN UNION’S ECONOMIC SANCTIONS: THE RESPONSE TO UKRAINIAN CRISIS DEVIDO PROCESSO DE LEI NAS SANÇÕES ECONÔMICAS DA UNIÃO EUROPEIA: A RESPOSTA À CRISE UCRANIANA - Bijos, Leila; Oliveira, Luiz Fernando de; Bragança, Thainá Ferreira Monteiro de (Caderno de Relações Internacionais, 2020)
This article focuses on the economic sanctions and the listing process in the light of due process of law, as well as the legitimacy of the European Union to impose such sanctions under international law. It has a qualitative approach, using the methodology of documental analysis (particularly the documents from the European Union Council and Commission) and bibliographical research. Since 2014 the European Union has imposed restrictive measures against the Russian Federation in response to the annexation of Crimea and Sevastopol, as well as ‘destabilization’ of Ukraine. Due to the imposition of these measures, 159 persons were subject to assets freezing and visa bans; 41 entities had their assets frozen in the EU; also including economic sanctions such as the limitation of Russian state-owned financial institutions to the European capital markets; and the access to ‘sensitive’ technologies, particularly in the energetic and military industries. As a conclusion, the listing process has improved considerably in the past years to align itself with the principle of due process. Critically, it is indicated the need to allow the targets to be heard and present their defense before any measures taken and in urgent matters which by its nature demand inaudita alteram parte decisions, the provision of injunctive relief.